Fumitremorgin C alleviates advanced glycation end products (AGE)-induced chondrocyte inflammation and collagen II and aggrecan degradation through sirtuin-1 (SIRT1)/nuclear factor (NF)-κB/ mitogen-activated protein kinase (MAPK). Issue 2 (1st February 2022) - Zhou, Yeli; Li, Jing; Wang, Chenglong; Pan, Zheer
ABSTRACT: Fumitremorgin C is a potent and selective inhibitor of the breast cancer resistance protein. This study aimed to explore the role of fumitremorgin C in osteoarthritis (OA) and disclose the underlying mechanism. The cell viability of AGE-treated SW1353 cells in the presence of fumitremorgin C was detected by Cell Counting Kit-8 (CCK-8) assay. The inflammation and extracellular matrix (ECM) deposition of AGE-induced SW1353 cells was respectively measured by enzyme linked immunosorbent assay (ELISA), immunofluorescence, and Western blot. The expression of SIRT1 and NF-KB/MAPK signal was examined by Western blot. After that, SIRT1 inhibitor EX527 was added to observe the mechanism of action of fumitremorgin C. Fumitremorgin C restored the cell viability of SW1353 cells injured by AGE. Furthermore, it alleviated inflammation and ECM degradation in AGE-induced SW1353 cell. The SIRT1 expression decreased by AGE was recovered upon fumitremorgin C to SW1353 cells. The ratio of phosphorylated p65 (p-p65) and p65, phosphorylated JNK (p-JNK) and JNK, and phosphorylated 38 (p-38) and 38 were increased by AGE treatment, which was recovered by fumitremorgin C addition. SIRT1 inhibitor EX527 reverts the repressive effects of fumitremorgin C on inflammation and ECM degradation in AGE-induced SW1353 cell. In conclusion, fumitremorgin C alleviates AGE-induced inflammation and the degradation of collagen II and aggrecan through SIRT1/NF-κB/MAPK, which reveals the underlying mechanism by which fumitremorgin C alleviates OA. Graphical abstract: uf0001